ANALYSIS OF STUDENTSâ EPISTEMOLOGICAL OBSTACLES ON THE SUBJECT OF PYTHAGOREAN THEOREM - Hutapea, Maya L; Suryadi, Didi; Nurlaelah, Elah (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2015)
This article explains mistakes made by junior high school students in solving Pythagorean Theorem problems as well as analysis of studentsâ difficulties in applying mathematical concepts (epistemological obstacles), in which these were reflected in their test answers. This research used descriptive exploratory method to describe symptom and phenomena, which occurs within the studentsâ mind while solving the problem. Data were obtained from a test of Pythagorean Theorem problems given to 99 students from three different schools clusters. Results suggested that students tends to use a quick way to solve the problems without adequate understanding of the concept, remember the term alone without a profound understanding of the concept, fail in solving the problems with implicit information and the problem that requires visual representation in the process of solving the problem. Students also did not like the word problems or a problem with long questions. Teachers play a pivotal role in helping the students to overcome epistemological obstacles such as by giving the students more exercises as well as using different tools and technique in teaching the concept.Keywords: learning obstacles, epistemological obstacles, pythagorean theoremABSTRAKArtikel ini menyajikan kesalahan yang dilakukan oleh siswa sekolah menengah pertama dalamÂ  menyelesaikan soal-soal terkait teorema phytagoras dan juga analisis mengenai kesulitan siswa dalam mengaplikasikan konsep matematik (epistemological obstacle). Kesalahan-kesalahan ini dapat dilihat dari jawaban yang diberikan siswa pada tes yang diberikan. Penelitian ini menggunakan pendekatan deskriptif untuk menjelaskanÂ  fenomena yang terjadi pada siswa dalamÂ  menyelesaikan soal-soal terkait teorema Phytagoras. Data yang diperoleh pada penelitian ini berasal dari hasil tes soal-soal Teorema phytagoras yang diberikan pada 99 siswa dari tiga cluster sekolah yang berbeda. Hasil analisis menunjukkan bahwa siswa cenderung menggunakan cara cepat untuk menyelesaikan persoalan tanpa memahami konsep, mengingat rumus secara utuh tanpa pemahaman yang mendalam terkait konsep phytagoras, gagalÂ  menyelesaikan soal yang memuat informasi yang implisit dan soal yang memuat informasi yang disajikan secara visual. Hasil wawancara menunjukkan bahwa siswa tidak suka soal cerita dan soal yang disajikan secara panjang lebar. Guru memainkan peran yang sangat penting dalam membantu siswa untuk mengatasi epistemological obstacle seperti dengan memberikan siswa latihan soal serta menggunakan berbagai media dan teknik pengajaran dalam mengajarkan konsep.Kata kunci: kesulitan belajar,Â  kesulitan epistemologis, teorema phytagoras